2016
DOI: 10.1080/21642850.2015.1135293
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in adolescents and young adults with type 1 diabetes: associations with diabetes management and glycemic control

Abstract: Objective To describe sleep in adolescents and young adults with type 1 diabetes and explore the association between sleep disturbances, diabetes management and glycemic control. Methods Adolescents with type 1 diabetes (n = 159, mean age = 16.4, 43% female, 69% white, mean A1C = 9.3%) completed the Pittsburgh Sleep Quality Index to assess sleep quantity and quality and sleep disturbances. Frequency of blood glucose monitoring (meter downloads) was used as a measure of diabetes management. Results Average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 22 publications
(27 reference statements)
2
47
2
Order By: Relevance
“…In addition, we found that adolescents indicated more regular BGM at bedtime on weekend nights than on school nights, but the difference in frequency was not statistically significant. Although the difference was non-significant, it could be a reflection of having a more rushed schedule during the school week, or that that insufficient sleep on school nights negatively impacts adolescents’ ability to effectively engage in diabetes management, similar to findings from previous studies (14, 17). Another strength of our study is that by taking a multi-method approach, we were able to explain some of the disturbances observed in the actigraphy data; for example, several of the participants had night wakings that we could match to reports in the sleep diaries of treating low BG values overnight.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, we found that adolescents indicated more regular BGM at bedtime on weekend nights than on school nights, but the difference in frequency was not statistically significant. Although the difference was non-significant, it could be a reflection of having a more rushed schedule during the school week, or that that insufficient sleep on school nights negatively impacts adolescents’ ability to effectively engage in diabetes management, similar to findings from previous studies (14, 17). Another strength of our study is that by taking a multi-method approach, we were able to explain some of the disturbances observed in the actigraphy data; for example, several of the participants had night wakings that we could match to reports in the sleep diaries of treating low BG values overnight.…”
Section: Discussionsupporting
confidence: 77%
“…One study (Jaser & Ellis, 2016) did not yield a significant correlation between TST and glucose control, but sleep quality and HbA1c were related among male adolescents. Our previous cross-sectional study supported that shorter sleep duration related to higher HbA1c levels in 10 to 16 year olds (Perfect, 2014).…”
Section: Diabetes and Sleep Insufficiencymentioning
confidence: 96%
“…In contrast, McDonough et al found that for adolescents using insulin pumps, an increase in sleep duration of as little as 15 to 20 minutes resulted in an additional BG check or insulin administration the following day [•20]. Similarly, Jaser and Ellis found BG monitoring was positively associated with sleep duration in adolescents [21]. When analyzed by gender, they found that for males, better diabetes management (BG monitoring) was related to longer sleep duration [21].…”
Section: Impact Of Sleep On Diabetes Carementioning
confidence: 99%
“…Similarly, Jaser and Ellis found BG monitoring was positively associated with sleep duration in adolescents [21]. When analyzed by gender, they found that for males, better diabetes management (BG monitoring) was related to longer sleep duration [21]. …”
Section: Impact Of Sleep On Diabetes Carementioning
confidence: 99%